Eucalyptus Oil Simple Vapor Inhalation Therapy on Reducing Breathing Frequency in Children with Pneumonia - Mustofa, Sri; Cahyaningrum, Etika Dewi (PROMOTOR, 2024)
Acute inflammation in pneumonia is the result of an acute respiratory infection that is usually accompanied by coughing, shortness of breath and inflammation of the lung parenchyma. This can lead to increased secretion production and often causes the main problem of ineffective airway clearance. The purpose of this scientific work is to determine the effect of simple eucalyptus oil vapor inhalation therapy in reducing the frequency of breathing in children with pneumonia. The main ingredient in eucalyptus oil is the compound cineole (eucalyptol) which is known for its anti-inflammatory, antioxidant, bronchodilating (relieving the airway), antiviral and antimicrobial effects. This effect of cineole also has a mucolytic effect (dilutes phlegm) so that the secretion becomes thinner and easier to remove. The method used is a case study by going through the stages of the nursing process including assessment, diagnosis, intervention, implementation and evaluation. The purpose of this scientific work is to determine the effect of simple steam inhalation therapy on reducing the frequency of breathing. The nursing care process was carried out for 3 days starting April 22, 2024 - April 24, 2024. The results of the nursing care process that has been carried out, it is found that simple steam inhalation therapy with eucalyptus oil is effective for reducing the frequency of breathing in patients with airway clearance problems.